2011
DOI: 10.4317/medoral.16970
|View full text |Cite
|
Sign up to set email alerts
|

Do third molars weaken the mandibular angle?

Abstract: Objective: The purpose of this study is to estimate how is the magnitude of the impact of a mandibular third molar on the mandibular angle stiffness. Study Design: It was performed a literature search on whole MEDLINE and LILACS data base to find articles that match the following inclusion criteria: cohort studies presenting data on patients with mandibular fractures and third molars; that had a similar angle fracture definition; and that present data available to be cross-classified in a statistic analysis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…As punches often hit the mandible, this may well be the reason for the high number of wisdom teeth involved; wisdom teeth play an important role as a weak point in the mandible, making it prone for fractures of the mandibular angle (26)(27)(28).Motor vehicle accidents in our study totaled only 13%. Given that this group plays the main role for dental or maxillofacial traumatization in studies (15,18,29) from other countries, this number might be an argument for the high security standard, including the obligation to buckle up or wear protective headgear as a motorcyclist.…”
Section: Discussionmentioning
confidence: 70%
“…As punches often hit the mandible, this may well be the reason for the high number of wisdom teeth involved; wisdom teeth play an important role as a weak point in the mandible, making it prone for fractures of the mandibular angle (26)(27)(28).Motor vehicle accidents in our study totaled only 13%. Given that this group plays the main role for dental or maxillofacial traumatization in studies (15,18,29) from other countries, this number might be an argument for the high security standard, including the obligation to buckle up or wear protective headgear as a motorcyclist.…”
Section: Discussionmentioning
confidence: 70%
“…Retrospective studies, case series and literature reviews have shown that the presence of third molars is linked to the increased prevalence of mandibular angle fracture. 6 There are not enough studies from the perspective of biomechanics, which show the true impact of third molar presence and the occurrence of fractures, because reproducing a real model of the mandible is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…4 An experimental study with monkeys has shown that mandibles containing unerupted third molars fractured at approximately 60% of the force required to fracture mandibles with erupted third molars. 5 Bezerra et al 6 reported a 1.94fold higher risk of mandibular angle fractures when the third molar is present.…”
mentioning
confidence: 99%
“…There are various studies suggesting that mandibular third molar (M3) contributes to the weakness of the angle region of the mandible and increase the risk of its fracture for even two to fourfolds . Bezerra et al . noticed that traumatic impacts of lower intensity (such as assaults and sport injuries) resulted in energy transmission along the lesioned body and were more frequently associated with mandibular angle fractures, especially in cases with third molar.…”
mentioning
confidence: 99%